1974
DOI: 10.1002/1097-4679(197401)30:1<49::aid-jclp2270300111>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between differential levels of parental “pathogenesis” and male children's diagnoses

Abstract: PROBLEMKaren's'') conceptualization of the "pathogenic" relationship between the male schizophrenic child and his mother appears to have received empirical support in several studies ( * * 3 , 4 , in which ('pathogenesis" was defined operationally, through the use of the TAT, as an interaction between two persons in which the dominant individual either ignores the expressed needs of the dependent individual or meets his own needs a t the expense of the dependent individual. I n each case, mothers of male schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Souvent décrits comme perturbés et destructifs (Imura, Kwakubo, Mochizuki, Misu et Makihara, 1974;Mitchell, 1974), ces parents pourraient être ignorés ou même traités avec un certain dédain par certains professionnels de la santé mentale, sous prétexte qu'ils sont responsables des problèmes graves de leurs enfants. De plus, au niveau plus ou moins conscient, ces parents croient avoir échoué auprès de leurs enfants.…”
Section: Démarcheunclassified
“…Souvent décrits comme perturbés et destructifs (Imura, Kwakubo, Mochizuki, Misu et Makihara, 1974;Mitchell, 1974), ces parents pourraient être ignorés ou même traités avec un certain dédain par certains professionnels de la santé mentale, sous prétexte qu'ils sont responsables des problèmes graves de leurs enfants. De plus, au niveau plus ou moins conscient, ces parents croient avoir échoué auprès de leurs enfants.…”
Section: Démarcheunclassified
“…For specific purposes, as in research where one wishes to investigate only a single specified aspect of personality, or in clinical applications where one is interested in a single predetermined aspect of personality, that is not a problem. Then, one can develop specific, reliable, and accurate scoring paradigms that work empirically (e.g., Meyer & Karon, 1967; Mitchell, 1974; Wynne & Singer, 1963). However, in examining an individual where what is most relevant may not be known in advance, clinical thinking is essential.…”
Section: The Problem: What Is “Clinical” Data and How To Use Itmentioning
confidence: 99%
“…Mothers of schizo phrenics average pathogenesis scores of 75%; mothers of schizophrenics do not always ignore the conflicting needs of their children, but the more consistent problem makes children vulnerable. Singer and Wynne made available to Mitchell their TAT data from their National Institute of Mental Health study (Singer & Wynne, 1965b), and Mitchell found again that blindly scored TATs differentiated mothers of schizophrenics from mothers of normals (Mitchell, 1974).…”
Section: Pathogenesismentioning
confidence: 99%